Surgical approaches to canine appendicular osteosarcoma part 1- anatomic landmarks and amputation techniques - Borges, Ryshely Sonaly De Moura; da Silva, Paloma Helena Sanches; Pimentel, Pedro Antônio Bronhara; Pereira, Renato Dornas de Oliveira; Almendros, Angel; Giuliano, Antonio; Horta, Rodrigo dos Santos; Marinho, Paulo Vinícius Tertuliano (Frontiers in Veterinary Science, 2025)
Osteosarcoma (OSA) is the most common primary bone neoplasm affecting dogs and the appendicular bones are frequently affected, accounting for up to 80% of reported cases. After tumor diagnosis and staging, surgery followed by adjuvant chemotherapy is the standard treatment of care. The purpose of this narrative literature review is to describe the anatomical landmarks and amputation techniques performed in the treatment of canine appendicular OSA, also using cadaveric models to demonstrate it. Surgical treatment options may include amputation of the affected limb, considered the standard of care. For thoracic limbs anterior quarter amputation, amputation with shoulder disarticulation, and midhumeral amputation. For pelvic limbs, amputation with hemipelvectomy, amputation with hip disarticulation, and midfemoral amputation. Anatomical knowledge is fundamental for performing a meticulous and correct technique, which allows a lower risk of recurrence and intra-operative and post-surgical complications.